Enhancing SDS-PAGE Detection of Dilute Extracellular Polystyrene Degrading Enzymes Expressed by Bacillus megaterium Strain via Centrifugal Freeze Concentration Method - Tan, Kian Meng; Fauzi, Noor Akhmazillah Mohd; Kassim, Angzzas Sari Mohd; Rehan, Aisyah Mohd (Trends in Sciences, 2022)
This study aims to enhance the sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) detection and visualization of extracellular polystyrene degrading enzyme expressed by Bacillus megaterium as a result of utilizing polystyrene as a sole carbon source. Dilute polystyrene degrading enzyme expressed in the culture supernatant could not be directly visualized from SDS-PAGE stained with colloidal Coomassie blue stain as it falls below its sensitivity or detection limit level. To overcome this problem, the crude enzyme extract was concentrated via the centrifugal freeze concentration method (cryoconcentration). The extracellular enzyme profiles were determined by SDS-PAGE. The SDS-PAGE analysis of the concentrated enzyme extract revealed 6 visible protein bands ranging in size from 10 to 60 kDa. Three distinct protein bands at approximately 20, 45 and 60 kDa were observed to be highly expressed in the culture supernatant. Polystyrene degrading enzyme extracted from the culture supernatant was closely related to several polymer degrading enzymes which suggest that the extracted enzyme from Bacillus megaterium also belongs to the hydrolase’s enzyme family. GC-MS analysis of the extracted samples significantly contains benzene derivatives due to the breaking down of the long-chain aromatic hydrocarbon polymer. Hydroxylation of the aromatic ring formed phenolic substrate took place which suggests being facilitated by intracellular enzyme hydroxylases. Hence, the biodegradation of polystyrene by Bacillus megaterium was believed to incorporate both intracellular and extracellular enzymes. HIGHLIGHTS Bacillus megaterium strain was first reported to contribute to polystyrene biodegradation Polystyrene degrading enzyme expressed by Bacillus megaterium was detected through SDS-PAGE Cryoconcentration enhanced SDS-PAGE protein detection The protein bands were most distinct visualized at approximately 20, 45 and 60 kDa by SDS-PAGE GC-MS analysis detected benzene derivatives which confirmed enzymatic degradation activity GRAPHICAL ABSTRACT